Developments in Religious Education During the Transition Period to Pluralist Democracy in Turkey - Ayşe Çalal (Dini Araştırmalar)

(untitled)
By the republic era, it could be said that the most important reform, we may call “milestone in the field of education”, is the law ofTawhēd - Tadrīsāt, enacted in March three 1924 to remove themaktab-madrasahpredicament from the system of education. After the date it was enacted, fourth article of the mentioned law which urges the officials to educate religious scholars in a divinity faculty and to separate schools for educating Imams has been a starting point for the discussions that were to be argued over the religious education. Although there was no such a direct enforcement within the text of the law regarding to the shutting down of themadrasahschools (schools which were once the touch stone of the Ottoman education system), they were still shut down and later a divinity faculty was established along with the religious vocational schools in different cities of Turkey.After this date, many regulations came into existence in regard to the religious education and religion classes. However, the institutions of religious education established according to the regulations done until 1939 were shut down and the religion classes in the syllabus were gradually cancelled. For the state abandoned the religious education of its formal education system, a need emerged by time for religious education but the absence of it raised the tension of the societyagainst the state.By the end of Second World War and the transition process to the pluralist democracy in Turkey provided the environment to the people to enunciate their desire for the state to take over the religious education and organize it under the formal education. In the light of this situation, many regulations were done from 1946 to 1960. Within the frame of this article, the period of time witnessed massive amount of development in religious education is chronologically probed and summarized via descriptive method.